Statistical inference in behavior analysis: Discussant's remarks - Shull, Richard L. (1999)
A collection of essays on the roles of inferential statistics in behavior-analytic research prompted consideration of five issues: (a) the acceptance of research that focuses on the behavior of individual organisms; (b) the need to apply methods thoughtfully; (c) the heuristic value of statistical description; (d) the treatment of aberrant data in the search for general principles; and (e) the role of derived measures in the search for invariances.